Digital Transformation of MSMEs: An Accounting Review of the Impact of E-Commerce on Revenue and Financial Performance - Reksadini, Marda Ulya; Prasetya, Rizka Fajriana Fitri; Azmi, Khoirul (AKTSAR: Jurnal Akuntansi Syariah, 2025)
This study examines the impact of digital transformation through e-commerce adoption on turnover and financial performance of micro, small, and medium enterprises (MSMEs) in Kota District, Kudus Regency, Central Java, from an accounting perspective. A quantitative survey was conducted with 51 MSMEs selected using purposive sampling from a population of 103. Primary data were collected via a 1–4 Likert scale questionnaire and analyzed using linear regression and paired-sample t-tests to compare turnover before and after e-commerce adoption. The results indicate that e-commerce has a positive and significant effect on both turnover and financial performance; average turnover increased from IDR 1,193,180 to IDR 1,527,450, a 28% rise. Although only 20% of respondents integrated their accounting systems with e-commerce platforms, digital adoption enhanced transaction recording efficiency, financial reporting transparency, and profitability analysis capabilities. These findings highlight the contribution of digital transformation and accounting system integration in improving MSME financial management, providing practical guidance for digital strategy implementation in Kudus.